2022
DOI: 10.1109/jsen.2022.3193504
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of an Urban LoRaWAN Deployment: Real World Versus Simulation

Abstract: LoRaWAN simulations are a flexible way to analyse the behaviour of this LPWAN technology in scenarios that are unfeasible to deploy due to their scale and the number of devices required. Parallel to this, there is also a continued lack of largerscale LoRaWAN deployments in current literature. Crucially, none of these studies involves comparison with any theoretical model, such as discrete-time simulation or mathematical analysis, for validation. In this paper we deploy a 20 nodes LoRaWAN network around the Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Finally, the size of the payload and the intermediate period of creation and sending messages from each ED (uplink) as well as the total simulation time of the test are noted. ADR will be disabled in all cases because in some cases it caused more issues than it solved [ 28 ]. It is found that while ADR decides to update SF for a node based on channel conditions, it does not consider the impact of collisions resulting from the increasing number of nodes within the same network [ 29 ] to be able to manually control parameters independently.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the size of the payload and the intermediate period of creation and sending messages from each ED (uplink) as well as the total simulation time of the test are noted. ADR will be disabled in all cases because in some cases it caused more issues than it solved [ 28 ]. It is found that while ADR decides to update SF for a node based on channel conditions, it does not consider the impact of collisions resulting from the increasing number of nodes within the same network [ 29 ] to be able to manually control parameters independently.…”
Section: Methodsmentioning
confidence: 99%
“…Typically, LoRa technology has been deployed as a hub and spoke topology based on the Layer 3 LoRaWAN protocol [14]. LoRa exhibits substantial potential, particularly as a candidate for a long-range multi-hop network.…”
Section: Related Workmentioning
confidence: 99%
“…Besides, a simulation called LoRa-MAB focuses on transmission rates [15]. Furthermore, comparative LoRaWAN network analysis between physical and simulation results are also available [16].…”
Section: Introductionmentioning
confidence: 99%